Enhanced Bandwidth of Band Pass Filter Using a Defected Microstrip Structure for Wideband Applications - Sanae Azizi; Mustapha El Halaoui; Abdelmoumen Kaabal; Saida Ahyoud; Adel Asselman (International Journal of Electrical and Computer Engineering (IJECE), 2018)
In this paper, the bandwidth enhancement of bandpass filter (BPF) is proposed by utilizing defected microstrip structure (DMS). The initial micro strip BPF which is designed to have the bandwidth 1GHz with the center frequency of 3.5GHz is deployed on FR4 Epoxy dielectric substrate with overall size and thickness of 14mm x 24mm and 1.6mm, respectively. The proposed filter consists of two parallel coupled lines centred by ring-shaped, to enhance the bandwidth response, an attempt is carried out by applying DMS on the ligne center with a ring-shaped of initial filter. Here, the proposed DMS is constructed of the arrowhead dumbbell. Some parametrical studies to the DMS such as changing to obtain the optimum geometry of DMS with the desired bandwidth response. From the characterization result, it shows that the utilization of DMS on to the microstrip ligne of filter has widened 3dB bandwidth response up to 1.8GHz ranges from 2.55GHz to 4.35GHz yielding an enhanced wideband response for various wideband wireless applications.